Evolutionary History of Bats : Fossils, Molecules and Morphology. - Gunnell, Gregg F. (Cambridge Studies in Morphology and Molecules: New Paradigms in Evolutionary Bio., 2012)
Explores the rich evolutionary history of bats from multiple perspectives, presenting some of the most remarkable discoveries involving fossil bats.